Closed linguistic space censorship by the occupation forces and postwar Japan - Eto?, Jun 1933-1999; Kokusai Mondai Kenkyu?jo; Shuppan Bunka Sangyo? Shinko? Zaidan (2020)
The United States postwar occupation of Japan likes to boast of having given the Japanese freedom of expression and freedom of the press. True, it freed the Japanese press from many wartime constraints. But at the same time, it imposed a large number of new constraints, replacing wartime censorship by the Japanese government with postwar censorship by the American occupation authority. Even before the war ended, planning for the occupation included a censorship and public relations effort that would work to "re-educate" the Japanese and fold them into the postwar American international order. Similar efforts were made in Germany, but the effort in Japan was far more sweeping and far more sustained. This book documents that history in detail with extensive references to primary resources held in U.S. archives and elsewhere. Was the occupation successful in reshaping the Japanese mindset? Citing not only the postwar Constitution but also, among other things, the widespread belief in the Tokyo Trials' validity, Eto? argues doggedly that it was so successful that its pernicious influence persists even today. Yet the heart of this heavily researched book is its meticulous documentation of how this censorship was planned and enforced."--Dust jacket.
How the United States Prepared for Censorship in Japan. Introduction ; Wartime Planning ; Censorship's Justification ; Inner Workings ; The Language Factor ; The Basic Plan -- How the United States Conducted Censorship in Japan. An Invisible Cage ; Press Censorship ; Shared Taboos ; Perspectives in a Closed Linguistic Space ; War Guilt ; The Tokyo Trials ; Dissenting Voices ; Germany and Japan ; Internalization ; The Politicization of Language -- Afterword -- Afterword to the Paperback Edition.
Originally published in Japan by Bengeishunju Ltd. under the title of Tozasareta gengo ku?kan, 1989.
Translated by The Japan Institute of International Affairs (JIIA)."--Page 4.
Includes bibliographical references.
Japanese names are given in Japanese order, family name first." Original Japanese edition included translated quotations from English, some of which have here been retranslated to English.--Page 4.
Keywords: 1948-1989.; Freedom of the press -- Japan -- History; Censorship -- Japan -- History; Tokyo Trial, Tokyo, Japan, 1946-1948.; Postwar reconstruction -- Japan; Censorship; Freedom of the press; Politics and government; Postwar reconstruction; Japan -- Politics and government -- 1945-1989.; Japan -- History -- Allied occupation, 1945-1952.; Japan -- Foreign relations -- United States; United States -- Foreign relations -- Japan; Japan -- History